Portuguese adults’ concerns on the return to indoor sports practice after confinement due to COVID-19 pandemic -mitigation strategies proposals - Matos, Rui (2021)
Objective: This study aimed to get an insight of Portuguese adult people concerns about returning to physical activity and sports practice at indoor sports facilities, after confinement due to COVID-19’ pandemic. Subsequently, an additional approach to the traditional mitigation strategies was to be proposed. Methods: A total of 173 Portuguese practitioners on indoor physical activity or sports before pandemic participated in this study. A questionnaire asking how much concerned (1 – nothing, to 5 – completely) would they be on different contexts and aspects related to this return was applied. Results: respondents were considerably concerned about this theme, especially with touching on common surfaces and proximity to others. Although considerable concerned if having to travel by public transport to the training facility, using locker rooms and with features of the sports’ practice itself, the former received the highest concerns. Additionally, we have suggested modifying some objects (or creating others) that may allow their use with body parts other than hands - an important contagion source - and exploiting the possibility of using intermediate instruments on objects and sports equipment manipulation, preventing users from touching their surfaces directly. Conclusion: touching on common surfaces and proximity to others revealed high degrees of concern on the return to indoor sports practice after confinement due to COVID-19 pandemic. Alongside the rules of personal distancing, respiratory etiquette and surfaces hygiene, it is suggested that sports practitioners, whenever possible, use alternative body parts and intermediate instruments that avoid direct contact of hands with surfaces and sport objects.